Karakterisasi Dini Reservoar Seismik di Klaster Lapangan âTulipâ, Blok Lepas Pantai Belanda, Laut Utara - , Zulfadli, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Early Seismic Reservoir Characterization is a proposed method/workflow for exploring hydrocarbon fields based on 3D seismic and well log data. This method adopts the concept of reservoir characterization on development and production phases to be applied on exploration phase. The method utilizes advanced seismic interpretation techniques and applies the concept of anticipating risk and optimizing data as the power of interpretation. The characterization steps begin with DHI skimming, followed by spectral decomposition (Continuous Wavelet Transform/CWT), seismic inversion (Seismic Colored Inversion/SCI), porosity inversion (Supervised Neural Network), and completed with cross validation from Bayesian inversion (Probability Density Function/PDF). The method was tested on 3D seismic dataset of Dutch Offshore Block, North Sea. The study result showed existence of some speculative fields as âTulipâ Field Cluster on Upper North Sea Group. âTulip Alphaâ was the best speculative field that showed continuous consistency for prospective level and was confirmed until the last step. âTulip Alphaâ exposed strong bright spot and flat spot, was connected with normal fault, had good spectral decomposition and seismic inversion responses associated with hydrocarbon accumulation, and had good inversion porosity value (>35%). The study result showed real contribution of Early Seismic Reservoir Characterization for identifying hydrocarbon-bearing speculative fields on exploration phase quickly and effectively.